The use of "drones" and International Humanitarian Law: Some Issues - García-Rico, Elena del Mar (My University, 2018)
The use of "drones" has grown over the past decade, giving rise to a host of legal and other issues. At the international level, their use as means of warfare may entail significant risks for civilian protection and may challenge existing rules of International Humanitarian Law. As rapid advances continue to be made in new and emerging technologies of warfare, particularly those relying on "lethal" autonomous weapons systems, it is important to identified many of the humanitarian and legal issues raised by these weapons. The purpose of this paper is to attempt to outline some aspects of the international legal framework applicable to the use of drones in situations or armed conflict, including their implications for existing norms of International Humanitarian Law prohibiting or limiting the use of certain weapons.
Keywords: Derecho humanitario; Drones; International Humanitarian Law; Armed drones